The Role of the Eu3+ Concentration on the SrMoO4:Eu Phosphor Properties: Synthesis, Characterization and Photophysical Studies - Marques, Ana Paula A.; Tanaka, Marcos Takashi S.; Longo, Elson [UNESP]; Leite, Edson R.; Viana Rosa, Ieda Lucia (Springer/plenum Publishers, 2011)
SrMoO4 doped with rare earth are still scarce nowadays and have attracted great attention due to their applications as scintillating materials in electro-optical like solid-state lasers and optical fibers, for instance. In this work Sr1-xEuxMoO4 powders, where x = 0.01; 0.03 and 0.05, were synthesized by Complex Polymerization (CP) Method. The structural and optical properties of the SrMoO4:Eu3+ were analyzed by powder X-ray diffraction patterns, Fourier Transform Infra-Red (FTIR), Raman Spectroscopy, and through Photoluminescent Measurements (PL). Only a crystalline scheelite-type phase was obtained when the powders were heat-treated at 800 A degrees C for 2 h, 2 theta = 27.8A degrees (100% peak). The excitation spectra of the SrMoO4:Eu3+ (lambda(Em.) = 614 nm) presented the characteristic band of the Eu3 + 5L6 transition at 394 nm and a broad band at around 288 nm ascribed to the charge-transfer from the O (2p) state to the Mo (4d) one in the SrMoO4 matrix. The emission spectra of the SrMoO4:Eu3+ powders (lambda(Exc.) = 394 and 288 nm) show the group of sharp emission bands among 523-554 nm and 578-699 nm, assigned to the D-5(1)-> F-7(0,1and 2) and D-5(0)-> F-7(0,1,2,3 and 4), respectively. The band related to the D-5(0)-> F-7(0) transition indicates the presence of Eu3+ site without inversion center. This hypothesis is strengthened by the fact that the band referent to the D-5(0)-> F-7(2) transition is the most intense in the emission spectra.
Keywords: Europium; Molybdate; Complex polymerization method; Photoluminescence